Medical and economic analysis of the impact of rheumatoid disease-associated disability on the country's economy in terms of implementation of pension reforms - A. M. Lila; R. O. Dreval; O. V. Inamova; V. V. Shipitsyn; A. N. Zabotina (Современная ревматология, 2019)
The paper presents the data of an original study evaluating the impact of disability associated with a number of rheumatic diseases (RDs) (rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis) on the country's economy, as well as their related losses of the state under the conditions of implementation of the upcoming pension reform (PR). The authors consider the socioeconomic importance of disability associated with RDs in the current period and after PR implementation in 2019–2028, determine the degree of its influence on the country's gross domestic product, and also calculate the economic efficiency of return of the potentially able-bodied proportion of disabled people (able-bodied population) to socioeconomic activity.The opinions of experts and leading experts in this area from different subjects of the Russian Federation were taken into account when preparing the study.